Transporte elétrico e magnetotransporte em carbono granular - Alex Aparecido Ferreira (2011)
In this work we have studied the electrical conduction between localizedstates in samples with dierent volumetric densities of carbon-black, a kind of granular carbon. Firstly, we have shown that the Mott's variable range hopping (VRH) model t our data in a large range of temperatures. At low temperatures, we can see a deviation to a larger exponent, whichseems to be the one from the Efros-Shklovskii's VRH, due to the Coulomb interactions between the charge carriers. However, the crossover between the both regimes is not clear: there is a temperature range which is tted by the both exponents. To overcome this issue, we have proposed an equation, considering the density of states which implies a thermally activated correction to the Mott resistivity equation at high temperatures, and connects smoothly to the ES equation, at low temperatures. We havetted our data using this equation, and we have concluded the ES's regime was not really achieved. The obtained conduction parameters are reasonable, and we argue that transport in carbon nanoparticles and agglomerates occur through localized states and that a soft gap is most probably to exist in the density of states, at the Fermi level, due to the Coulomb interactions. Secondly, we have studied how the electric transport properties are changed when an magnetic eld is applied. We have shown the general behavior of the magnetotranport in CB (when the magnetic eld H or the temperature T changes) is explained by the scattering of the electron wavefunctions due to other impurities when the electrons "hops"between two localized states. However, we have concluded the available models are not completely appropriate to explain our data, and some improvements in the models must be proposed.